â€œANAK SEHAT, ANAK GEMBIRAâ€ PAKET EDUKASI KESEHATAN ANAK USIA PRASEKOLAH TK STRADA DEWI SARTIKA III â€“ TANGERANG - BANTEN - Lia Kartika; Fiorentina Nova2,; Dora Irene Purimahua; Windy Sapta Handayani Zega (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2021)
ABSTRACTThe task of a child's independence in carrying out activities for himself is increasingly developing at preschool age, so parents need to know the development and achievement of children's abilities according to their age. This knowledge is needed so that parents can train children in achieving developmental tasks such as self-care and become a role model for children to practice good health behaviors, one of which is to maintain dental hygiene. The results of this educational package include 2 things. From the child's side, the results of education and demonstration about brushing teeth are that the child is able to mention the frequency and the right time to brush teeth, the impact if irregularly brushing teeth, the right time to replace the old toothbrush with a new one, and be able to show how to brush teeth as has been exemplified before. While in terms of parents, there was an increase in the average knowledge of parents before and after the provision of education by 27.68%. At the end of the activity, the parent participant expressed his desire to begin to recognize the child's developmental achievements according to his age. The conclusion of the health education activities provided is the increased ability of children to information about dental health and the willingness to perform self-care optimally according to their age stages. Furthermore, it is important to hold continuing education to realize the importance of monitoring the development of preschool children which includes language, psychosocial, psychosexual, cognitive, emotional, and spiritual development.Â